High But Not Low Probability of Gain Elicits a Positive Feeling Leading to the Framing Effect - Gosling, Corentin J.; Moutier, Sylvain (Frontiers in Psychology, 2017)
Human risky decision-making is known to be highly susceptible to profit-motivated responses elicited by the way in which options are framed. In fact, studies investigating the framing effect have shown that the choice between sure and risky options depends on how these options are presented. Interestingly, the probability of gain of the risky option has been highlighted as one of the main factors causing variations in susceptibility to the framing effect. However, while it has been shown that high probabilities of gain of the risky option systematically lead to framing bias, questions remain about the influence of low probabilities of gain. Therefore, the aim of this paper was first to clarify the respective roles of high and low probabilities of gain in the framing effect. Due to the difference between studies using a within- or a between-subjects design, we conducted a first study investigating the respective roles of these designs. For both designs, we showed that trials with a high probability of gain led to the framing effect whereas those with a low probability did not. Second, as affect is known to be central to the framing effect, we sought to determine whether it is responsible for such a debiasing effect of the low probability of gain. Our second study thus investigated the relationship between affect and the framing effect as a function of high and low probabilities. Our results revealed that positive affect was related to risk-seeking in the loss frame, but only for trials with a high probability of gain. Taken together, these results support the interpretation that low probabilities of gain suppress the framing effect because they prevent the positive affect of the anticipation of gain.